Applied Behaviour Analysis (ABA) as main intervention for autistic children - Syed Azman, Syarifah Zafirah (IIUM Press, 2022)
This article reviews Applied Behavioural Analysis (ABA) as one of the best intervention tools for children with an autism spectrum disorder. This intervention is highly suitable for implementing parents with children in the spectrum. In this article, we defined ABA as an intervention that ABA applies the basic principles of behaviours to teach wanted behaviours and remove unwanted behaviours. This article provides some examples of ABA practices that the parents can do at home. ABA helps improve different aspects of children development. Parents who conduct ABA at home, combined with a one-on-one session with a therapist, will provide the children with the best possible outcome for their product. Suggestions on ways to look for therapy centres and ABA centres contact details are also provided in this article.